Band Gap Engineering of Mg Doped ZnO Nanorods Prepared by a Hydrothermal Method - BOYRAZ, CİHAT (WILEY-V C H VERLAG GMBH, 2019)
The effect of band gap on the structure, magnetic, and optical properties of Zn1-xMgxO nanorods synthesized by hydrothermal method using varying x-values from 0.00 to 0.05 with 0.01 step increment is studied. The structural phases of Zn1-xMgxO samples are determined by X-ray diffraction tool. The Rietveld analysis is performed for the selected Zn0.95Mg0.05O sample and all samples' phases are found as single phase. The concentration-dependent of lattice parameters, cell volumes, microstrain, and dislocation density, locality of the atoms and their displacement, and bond length in Zn1-xMgxO structures are detailed. Electron Spin Resonance (ESR) measurements are performed and analyzed through concentration dependence of the g-factor and the line-widths of pike to pike (Delta H-PP) of ESR spectra. A ferromagnetic behavior of the Zn0.95Mg0.05O nanorods is observed. The optical band gaps (E-g) of Zn1-xMgxO nanorods are obtained by the data taken from Ultraviolet-Visible (UV-VIS) diffuse reflectance spectroscopy. It is found that the E-g-values increased with increasing amount of Mg elements in the structure.
Keywords: hydrothermal method; magnetic properties; nanorod; optical properties; zinc oxide; ELECTRICAL-PROPERTIES; OPTICAL-PROPERTIES; NANOSTRUCTURES; MGXZN1-XO; ESR